Comparison of Effects of Mothers' and Mozart's Lullabies on Physiological Responses, Feeding Volume, and Body Weight of Premature Infants in NICU - Shin, Hyo-Jin; Park, Jooyeon; Oh, Hye-Kyung; Kim, Nahyun (Frontiers in Public Health, 2022)
Objectives: The purpose of this study was to compare the effects of mothers' and Mozart's lullabies on physiological parameters, feeding volume, and body weight of premature infants in a neonatal intensive care unit (NICU). Methods: This study used a non-equivalent control group, non-synchronized design as a quasi-experimental study. Two intervention groups (recorded mother's lullaby and Mozart's lullaby) and a control group were formed from a total of 65 premature infants: a mother's lullaby group of 22 infants, a Mozart's lullaby group of 22 infants, and a control group of 21 infants not provided with any lullabies. Their physiological parameters included heart rate, blood pressure, respiratory rate, and O2 saturation. The infants’ feeding volume and body weight were measured as indicators related to the growth of premature infants. The mother’s and Mozart’s lullabies were played on a speaker in an incubator for 15 min for 7 consecutive days per group. Results: There were significant differences in the mean difference before and after intervention in neonatal heart rate (χ2=45.03, P<.001), systolic pressure (F=43.29, P<.001), diastolic pressure (χ2=33.01, P<.001), respiratory rate (F=76.06, P<.001), and O2 saturation (χ2=40.82, P<.001) between the three groups. The mean differences of both mother's and Mozart's lullaby groups were significantly higher than those of the routine care group in all physiological parameters, and those of the mother's lullaby group was significantly higher when compared with the Mozart's lullaby group. In repeated-measures ANOVA, there was a significant interaction between time and group in feeding volume (F=2.46, P =.041). However, body weight did not significantly differ in an interaction between time and group (F=1.75, P =.151). Conclusion: This study showed beneficial effects of mother's lullaby and Mozart's lullaby on physiological parameters. Especially, the mother's lullaby was found to significantly improve all physiological parameters and feeding volume of premature infants in the NICU compared to Mozart’s lullaby group. Therefore, we recommend the regular integration of the mother's lullaby into supportive care of premature infants in the NICU, as this intervention highlights the need for mothers to participate in their care.